2022
DOI: 10.1021/acs.molpharmaceut.1c00678
|View full text |Cite
|
Sign up to set email alerts
|

Forced Solid-State Oxidation Studies of Nifedipine-PVP Amorphous Solid Dispersion

Abstract: In the present study, the oxidative degradation behavior of nifedipine (NIF) in amorphous solid dispersions (ASDs) prepared with poly(vinyl pyrrolidone) (PVP) with a short (K30) and a long (K90) chain length was investigated. The ASDs were prepared via dry ball-milling and analyzed using Fourier transform infrared (IR) spectroscopy, X-ray scattering, and differential scanning calorimetry. The ASDs were exposed to accelerated thermal-oxidative conditions using a pressurized oxygen headspace (120 °C for 1 day) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…Given that the computational method is established herein, the future effort in calculating C–H BDE of the ionized state of the molecules can help in making a quick risk-assessment of autoxidation in solution state. Further, the BDE calculations of the H-bonded states of molecules can be relevant to the solid-state autoxidation propensities …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that the computational method is established herein, the future effort in calculating C–H BDE of the ionized state of the molecules can help in making a quick risk-assessment of autoxidation in solution state. Further, the BDE calculations of the H-bonded states of molecules can be relevant to the solid-state autoxidation propensities …”
Section: Discussionmentioning
confidence: 99%
“…The outcome of the present studies set the motivation for the next steps in this direction such as Given that the computational method is established herein, the future effort in calculating C–H BDE of the ionized state of the molecules can help in making a quick risk-assessment of autoxidation in solution state. Further, the BDE calculations of the H-bonded states of molecules can be relevant to the solid-state autoxidation propensities There has been a continual attempt in relating the thermodynamic descriptors to the kinetics (e.g., reaction rates).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between nifedipine molecules and PVP K-30 can occur during the process of making solid dispersions. Nifedipine molecules will be dispersed and trapped in the PVP polymer network, and when heated, the physical state of nifedipine can change into an amorphous form (Kothari et al, 2015;Saraf et al, 2022).…”
Section: Solid Dispersion Sample Preparationmentioning
confidence: 99%
“…33 Several reports have highlighted the unintended degradation of drugs induced via mechanoactivation during ambient or cryogenic dry milling such as that reported for praziquantel, 34 quinapril HCl, 35 gabapentin, 36 and furosemide. 37 Previous experiences from our lab have shown that some drugs (e.g., droperidol 38 and nifedipine 39 ) undergo autoxidation in the presence of polymers containing free radicals. Pas et al have reported in-process degradation of indomethacin due to the generation of free radicals by the polymer during cryo-milling of indomethacin− PVP.…”
Section: Introductionmentioning
confidence: 99%